Participation à la dynamique langagière et appartenance à la communauté linguistique: analyse du français parlé par des francophones et des anglophones de Montréal - Daveluy, Michelle (Université de Montréal, 1994)
Keywords: Langue

The Antiochan Orthodox Syrians of Montreal 1905-1980: an Historical Study of Cultural and Social Change Over Three Generations - Marino, Norman (Université Concordia, 1994)
Keywords: Syriens

Safeguarding Mother Tamil in Multicultural Quebec: Sri Lankan Legends, Canadian Myths, and the Politics of Culture - Brunger, Fern (Université McGill, 1994)
Keywords: Sri Lankais

Problèmes de communication interculturelle et ruptures des cadres chez des immigrants et immigrantes latino-américains à Montréal - Hudon, Nathalie (Université du Québec à Montréal, 1994)
Keywords: Latino-Américains

Proposition d'un cadre de recherche opérationnelle pour l'étude de la ségrégation résidentielle ethnique dans la région métropolitaine de Montréal - Bérubé, Sylvain (Université de Montréal, 1994)

Langage et ethnicité: communication interculturelle à Montréal, 1977-1991 - Moise, Lena C.; Bourhis, Richard Y. (Canadian Ethnic Studies / Études ethniques au Canada, 1994)
Number: 1
Keywords: Langue

The Education of Italians in Montreal, 1895 to 1960 - Gadler, Yves Carmelo Luciano (Université McGill, 1994)
Keywords: Italiens

L'attitude des chinois de Montréal vis-à-vis des stratégies ethniques des banques - Hakimian, Edith (École des hautes études commerciales de Montréal, 1994)
Keywords: Banques; Chinois

L'international, un devoir au quotidien depuis 1910 - Char, Antoine (Le Devoir: reflet du Québec au 20e siècle, 1994)
Keywords: Devoir (Le)

Anomie et délinquance chez un groupe d'adolescents anglais de la région métropolitaine de Montréal - Rivest, Jean (Université du Québec à Montréal, 1994)
Keywords: Anglophones; Délinquance

Constructing Italian Ethnicity: A Comparative Study of Two Italian Language Newspapers in Australia and Canada, 1947-1957 - Iuliano, Susanna (Université McGill, 1994)
Keywords: Italiens

Représentation de l'espace urbain et laïcisation de la pratique - Trépanier, Esther (Société, culture et religion à Montréal: XIXe-XXe siècle, 1994)

Afro-Canadian Activism in the 1960s - Stamadianos, Peter (Université Concordia, 1994)
Afro-Canadian activism became increasingly militant in the 1960s. The rise in militancy in the Afro-American leadership of the 1960s was one factor contributing to the new era of black politics in Canada. Increased immigration from the West Indies also encouraged the proliferation of Afro-Canadian organizations dedicated to challenging racial discrimination. Afro-Canadian activism, however, developed in a substantially different manner than black politics in the United States. On the whole, most Afro-Canadian organizations and leaders were considerably less militant in their tactics and strategies than their counterparts in the United States. Internecine divisions over ancestral origin were also more pronounced in Canada where the black population was ethnically heterogeneous when compared to the Afro-American community.
Keywords: Africains; Noirs

Femmes immigrantes et sida: les Haïtiennes de Montréal - Landry, Gervaise Patricia (Université Laval, 1994)
Keywords: Femmes; Haïtiens

Catholicisme romain ou catholicisme culturel? À propos de la messe et d'autres pratiques rituelles chez les francophones du Grand Montréal - Turcotte, Paul-André (Société, culture et religion à Montréal: XIXe-XXe siècle, 1994)

Residential Patterns of New Immigrants and Linguistic Integration - Montgomery, Catherine; Renaud, Jean (The Canadian Geographer / Le Géographe canadien, 1994)
Number: 4
Keywords: Langue; Quartiers

L'émergence d'une identité québécoise dans la dramaturgie anglo-montréalaise - Hulslander, Kenneth (Université du Québec à Montréal, 1994)
Keywords: Anglophones; Théâtre

Gender and Division of Labour in a Vietnamese-Canadian Buddhist Pagoda - Soucy, Alexander (Université Concordia, 1994)
Keywords: Femmes; Travail; Vietnamiens

Le comportement électoral des minorités au Québec lors des élections de 1976 - Jedwab, Jack (Bulletin de l'association québécoise d'histoire politique, 1994)
issued: 1994-21-00
Keywords: Anglophones; Élections

Family, Paesani and Networks: Politics and Economy of Montreal Italians - Aramaki, Michiko (Université McGill, 1994)
Keywords: Italiens

Un royaume en exil: le judaïsme montréalais - Anctil, Pierre (Société, culture et religion à Montréal: XIXe-XXe siècle, 1994)
Keywords: Juifs

Le «boom» des immeubles d’appartements à Montréal de 1921-1951 - Choko, Marc H. (Urban History Review / Revue d'histoire urbaine, 1994)
Number: 1
Keywords: Logement; Outremont; Westmount

Les Irlandais catholiques de Montréal: introduction historique et méthodologique - Slattery, Maureen (Société, culture et religion à Montréal: XIXe-XXe siècle, 1994)
Keywords: Irlandais